Impactos da abertura comercial sobre a pobreza e a desigualdade de renda no Brasil e suas regiões - 1986 a 2003 - Sidou Junior, Paulo Maria Othon (2007)
The aim of this study is to investigate the possible impacts of commercial integration on personal income inequality and poverty in Brazil and its regions, using a cross-section data for 21 states over 1986-2003. The theoretical basis came from the Hecksher-Ohlin. The effects of the urban concentration on poverty and inequality were also considered, once the internal migratory flows to the cities interfere in the labor market and press public services with negative consequences to social indicators. The results showed that the commercial opening effects were more visible when import and export (vis-à-vis GDP) are taken separately, instead they were considered together as usual in literature. The results also showed that increasing the ratio exports/GDP, the inequality in Brazil tends to reduce (by elevating the income of the 20% poorest people). However, from a regional point of view, increasing the ratio exports/GDP deteriorates the Gini coefficient in the states of Middle-West, increases the poverty rate in the Southeast and reduces it in the South. On the other hand, the imports increase comparatively to GDP tends to reduce the inequality in Brazil and in the Middle-West region; nevertheless it worsens the inequality indexes in the North region.